Homocysteine Role in Neural Tube Defect: A Review Paper (International Journal of Innovative Research in Engineering & Management, 2023)
Folic acid, when administered  periconceptionally, is now well recognized as having the  potential to prevent a variety of neural tube disorders. Folic  acid seems not to treat a nutritional deficiency in pregnant  women, according to a recent research. Rather, it seems that  these neural tube anomalies are caused by a metabolic flaw  or errors, which may be corrected with enough folic acid.  Folic acid seems to have the most influence on  homocysteine metabolism, according to a new research. We  observed that moms who were carrying diseased fetuses  had much greater homocysteine levels than those who were  not. These data suggest that one of the enzymes involved in  homocysteine metabolism is likely to be aberrant in  afflicted pregnancies. The conversion of homocysteine to  methionine may be the essential stage, according to animal  research. In cultured rat embryos, methionine is necessary  for neural tube closure. Homocysteine metabolism  necessitates the enzymes methionine synthase,  cystathionine synthase, and 5, 10 methylene  tetrahydrofolate reductase. If methionine synthase is the  dominant enzyme, vitamin B-12, such as folic acid, has a  higher chance of activating the aberrant enzyme, posing a  public health risk. Vitamin B-12 may find things simpler to  limit the amount of folic acid in fortified foods, reducing  the risk of folic acid overdose.
Keywords: Birth Defect; Folic Acid; Folate; Homocysteine; Neural Tube Defect